Total Hip Arthroplasty for Surgically Ankylosed Hips - Can, Ata; Yontar, Necip Selçuk; Erdoğan, Ayşe Övül; Erdoğan, Fahri (Cerrahpaşa Medical Journal, 2020)
Objective: This study aimed to evaluate the long-term results of total hip arthroplasty in patients with surgically ankylosed hips. Methods: We reviewed 8 hips of 7 patients in whom ankylosed hips were converted to total hip arthroplasty between October 2011 and November 2015. All patients had surgical ankylosis of their hips. All patients were evaluated regarding lumbar and contralateral hip pain, hip joint range of motion (ROM), functional status, and satisfaction from treatment after surgery. Results: In our study, the etiology of the ankylosis was tuberculous septic arthritis in 2 (25%) and developmental hip dysplasia in 6 (75%) hips. The mean duration of the surgical ankylosis before conversion surgery was 29±13.6 years. All patients had osseous ankylosis and the indications for arthroplasty were intractable low back pain in 6 patients (85.7%) and hip pain in 4 patients (57.1%). The mean follow-up period was 13±2.7 months. There was statistically significant improvement in lumbar and contralateral hip pain, hip joint ROM, functional status, and satisfaction from treatment after surgery. Conclusion: Conversion of hip ankylosis to total hip arthroplasty is an effective method to regain hip function and control symptoms of neighboring joints. Cite this article as: Can A, Yontar NS, Erdoğan AÖ, Erdoğan F. Total Hip Arthroplasty for Surgically Ankylosed Hips. Cerrahpaşa Medical Journal 2020; 44(2): 93-97.